Case Report: Botulism associated with cosmetic BoNT-A injections: respiratory failure and multidrug-resistant infection as emerging clinical challenges - Song, Yiming; Li, Jinyu; Ren, Yujiao; Zhang, Wei; Liu, Hongbo; Li, Zhenyi; Xu, Jiarui; Zhang, Xingguo; Liu, Dongxing; Zhou, Yi; Feng, Baobao (Frontiers in Pharmacology, 2025)
Botulism is a life-threatening neurotoxin-mediated disease characterized by flaccid descending paralysis which begins with cranial nerve palsies and might progress to extremity weakness and respiratory failure. Respiratory failure following cosmetic injections were scarcely reported due to the low dose of botulinum neurotoxin type A (BoNT-A) used. We present two cases of respiratory failure and multi-drug resistant (MDR) bacteria infection resulted from botulism following cosmetic injections. A 24-year-old female developed symptoms of dysphagia, blurred vision and dysarthria 6 days after cosmetic injections of BoNT-A, and progressed to respiratory failure which needed invasive mechanical ventilation 5 days later. Another 46-year-old female developed dizziness, headache and nausea 30 min after cosmetic injections of BoNT-A. Symptoms including ptosis, blurred vision, dysphagia, and slurred speech appeared 1 week later. The patient received mechanical ventilation due to the deteriorated respiratory failure. Both patients developed multi-drug resistant (MDR) bacteria infection during hospitalization. Though the pneumonia improved with effective antibiotics treatment, they underwent tracheostomy or second endotracheal intubation several days after successful weaning from the ventilator. Fortunately, they recovered without significant sequelae left. The widespread application of BoNT-A increases the risk of severe adverse events including respiratory failure and MDR bacteria infections. These two cases highlight the importance of pulmonary management for those with severe cosmetic botulism and health authorities’ supervision on the cosmetic injections with BoNT-A in the future.